2014
DOI: 10.7183/0002-7316.79.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Grand Challenges for Archaeology

Abstract: This article represents a systematic effort to answer the question, What are archaeology’s most important scientific challenges? Starting with a crowd-sourced query directed broadly to the professional community of archaeologists, the authors augmented, prioritized, and refined the responses during a two-day workshop focused specifically on this question. The resulting 25 “grand challenges” focus on dynamic cultural processes and the operation of coupled human and natural systems. We organize these challenges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(85 citation statements)
references
References 104 publications
0
68
0
4
Order By: Relevance
“…Research on Teotihuacan is important not only for what we learn about the city but also its state system, its foreign relations, and its legacy. Teotihuacan is a key site for comparative studies of urbanism and state formation-one of archaeology's ''grand challenges'' (Kintigh et al 2014;also Smith 2012). Research on Teotihuacan has shaped and been shaped by significant theoretical and methodological developments in archaeology.…”
Section: Introductionmentioning
confidence: 99%
“…Research on Teotihuacan is important not only for what we learn about the city but also its state system, its foreign relations, and its legacy. Teotihuacan is a key site for comparative studies of urbanism and state formation-one of archaeology's ''grand challenges'' (Kintigh et al 2014;also Smith 2012). Research on Teotihuacan has shaped and been shaped by significant theoretical and methodological developments in archaeology.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of pursuing innovation through the medium of grand challenges has seen several attempts in the general area of digital research in the UK and Europe (for examples, Huggett 2013: 18-19;Huggett 2015a: 81), as well as in nondigital areas. In archaeology, the best-known application is the American National Science Foundation-funded crowdsourcing project Planning Archaeological Infrastructure for Integrative Science which developed 25 challenges surrounding cultural processes and human/natural systems, and concluded that these were underpinned by a digital challenge: the need for online access to documented primary research data (Kintigh et al 2014;Kintigh et al 2015).…”
Section: Introducing Grand Challengesmentioning
confidence: 99%
“…Within academia, a bioarchaeology of kinship as social identity would be ideally positioned to contribute to one of the 25 most important scientific challenges for archaeology presented by Kintigh et al (2014). One of their 25 challenges (Challenge D2) concerns how people form social identities; specifically, the authors state that a critical aspect of future research will be understanding ''how human identities (vs. the modes of affiliation among other species) form with respect to biological and emotional bonds'' (Kintigh et al 2014, pp.…”
Section: Resultsmentioning
confidence: 99%